Further explore on the behaviors of IR electrochromism of a double layer constructed by proton acid-doped polyaniline film and ITO layer. (November 2019) - Zhang, Leipeng; Li, Damin; Li, Xiaobai; Wang, Bo; Xu, Gaoping; Zhao, Xin; Xia, Guiling; Gavrilyuk, Alexander; Zhao, Jiupeng; Li, Yao
Abstract: In this study, the IR electrochromic films were constructed by dodecylbenzene sulfonate acid (DBSA)-doped polyaniline (PANI) film and an indium tin oxide glass (ITO). We used the in situ electrochemical deposition method for preparing the DBSA-doped PANI. The IR electrochromic properties of the double layer structure have been investigated minutely. We discovered two operation modes of modulation IR emissivity of the double layer structure with the increase of thickness of the PANI layer. When the thickness of the PANI film was within a certain range, its switching between leucoemeraldine (LB) and emeraldine salt (ES) modulated IR transmittance of the PANI film to realize regulation of the IR emissivity of the double layer structure (Mode Ⅰ). When the thickness of the PANI film reached a certain value, its IR transmittance was lower, the IR emissivity modulation of the double layer structure was determined mainly by the IR reflectance of the PANI film which depended on the pseudo-metallic behavior of the PANI film (Mode Ⅱ). Graphical abstract: Two operation modes of modulation IR emissivity of the double layer structure with different thickness of the PANI layer and emittance spectra.Image 1 Highlights: The DBSA-doped PANI film with IR regulation ability was synthesized via in-situ electrochemical deposition. The relationship between the conductivity, IR transmittance, and IR emissivity of the PANI film was investigated. We proposed two operation modes to explain the behaviors of IR electrochromism of the PANI film on the ITO.